2021
DOI: 10.3390/beverages7020033
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals as Potential Targets for the Development of a Functional Beverage for Improving Sleep Quality

Abstract: Functional beverages can be a valuable component of the human diet with the ability to not only provide essential hydration but to deliver important bioactive compounds that can contribute to chronic disease treatment and prevention. One area of the functional beverage market that has seen an increase in demand in recent years are beverages that promote relaxation and sleep. Sleep is an essential biological process, with optimal sleep being defined as one of adequate duration, quality and timing. It is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 175 publications
0
5
0
Order By: Relevance
“…In 2014, the Chinese State Food Safety Commission approved theanine as a novel food and stipulated that the daily intake of theanine should not exceed 400 mg. Therefore, based on its health benefits, theanine has been widely applied in foods (such as bakery food, , mango sorbet, and beverages) and dietary supplements . Moreover, theanine inhibited AGE formation in the bovine serum albumin-MGO model system and in rats, but its mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the Chinese State Food Safety Commission approved theanine as a novel food and stipulated that the daily intake of theanine should not exceed 400 mg. Therefore, based on its health benefits, theanine has been widely applied in foods (such as bakery food, , mango sorbet, and beverages) and dietary supplements . Moreover, theanine inhibited AGE formation in the bovine serum albumin-MGO model system and in rats, but its mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, we referred to the fermented orange as functional since socalled "functional beverages" provide important bioactive compounds for maintaining health and/ or contributing to the prevention and treatment of chronic diseases (BULMAN et al, 2021;CONG et al, 2020;GONÇALVES et al, 2022). The "functional properties'' can be characterized by high polyphenol content, antioxidant potential, probiotics, and other characteristics (BULMAN et al, 2021;CUVAS-LIMÓN et al, 2022;PINTO & VILELA, 2021), even alcoholic beverages such as wine and beer have already been identified as functional beverages (RADONJIĆ et al, 2020). FOB had already demonstrated good antioxidant capacity in different in vitro evaluations (MASCARIN et al, 2023) and now it has demonstrated this property in vivo, which confirmed that FOB is indeed a functional beverage.…”
Section: Effect Of Fermented Orange Beverage On Etohinduced Changes I...mentioning
confidence: 99%
“…Table 1 shows the major classes of functional foods, from the nutraceutical context, and their associated bioactive components/effects. The functional food classification would include beverages (Nutraceutical beverages) (Saeed et al, 2019;Dí az et al, 2020;Bulman et al, 2021), fermented foods (Islam et al, 2019;Vasilean et al, 2021;Yun et al, 2021), fruits (Ellis, 2021;Lim et al, 2021), herbs and spices (Ahmad et al, 2020;Pandey et al, 2022;Chopra et al, 2022), honey (Anfang et al, 2018;Grüter, 2020;Berenbaum and Calla, 2021;Martinez-Armenta et al, 2021), legumes (Barman et al, 2018;Carrera et al, 2021), nuts (Del Gobbo et al, 2015;ARS, 2019;Ros et al, 2021), seafood (fishes) (Te ´ lessy, 2019; Ashraf et al, 2020;Ellis, 2021), seeds (Kawakami et al, 2015;Khosravi-Boroujeni et al, 2017;Robertson, 2017;Suryapal et al, 2021), vegetables (Saiwal et al, 2019;Arya et al, 2019), as well as whole grains (Priebe and McMonagle, 2016;Kelly et al, 2017;Zabolotneva et al, 2022), which will be further discussed in this section. Further illustrating the abovementioned, some vegetables with their associated nutraceutical potentials are presented in Table 2, in terms of plant species, image display, common cultivars and parts commonly used.…”
Section: Common Functional Foods From the Nutraceutical Context And T...mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t Some common nutraceutical beverages include tea/coffee, enhanced/mineral water, plant milks, fortified fruit drinks/juices, smart drinks, ready-to-drink teas, performance/sports drinks, dairy beverages, etc. (Corbo et al, 2014;Dí az et al, 2020;Bulman et al, 2021). Some beverages produced from nuts, herbs (medicinal plants), grains, seeds, etc.…”
Section: Common Functional Foods From the Nutraceutical Context And T...mentioning
confidence: 99%